Geographical Information System of Chocolate Plantation Locations in Berau District Using QGIS Web - Aulia Khoirunnita; Fajar Ramadhani; Reza Andrea (Politeknik Pertanian Negeri Samarinda, 2024)
The cultivation of cocoa plants in Berau Regency has been carried out traditionally with pre-conflict productivity of 700-800 kg/ha, but after the conflict and attacks PBK (Cocoa Fruit Borer) was reported to be only half. The yield quality is also low due to the pest attack and minimum post-harvest treatment. In addition, farmer institutions to be able to carry out activities in the garden together have not been well formed. According to Development Planning Agency at Sub-National Level of Berau Regency, in 2009 the area of cocoa plants in Berau Regency covered an area of 8,644 ha with a production of 2,362 tons. The area is spread across eight districts. With so many chocolate plantations in Berau regency, it certainly makes buyers or visitors, both from related ninas and individuals, become overwhelmed to find the location of chocolate plantations. Therefore, an application is needed to facilitate the search for location and data about the location you want to visit. Geographic Information Systems (GIS) or also known as Geographic Information Systems (GIS) have recently experienced significant developments along with the advancement of geographic information technology. GIS is a computer-based information system that combines map elements (geographical) and information about the map (attribute data) designed to obtain, process, manipulate, analyze, demonstrate and display special data to complete planning, processing and research problems. With the web-based designed GIS application, it is able to solve problems related to the vast chocolate plantation in Berau.